2010
DOI: 10.1139/o09-165
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial expression of PDECGF is associated with extracellular matrix remodeling in experimental myocardial infarction in rats

Abstract: Platelet-derived endothelial cell growth factor (PDECGF) is a potent angiogenic peptide with anti-apoptotic activity expressed widely in tumours. However, its expression in myocardial infarction (MI) is not yet established. This study aimed to assess the myocardial expression of PDECGF in rats after MI. Extracellular matrix (ECM) remodeling plays an important role in angiogenesis; hence, changes in the ECM components were investigated in the myocardium after MI, which was induced in rats by coronary artery lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Thymidine phosphorylase is an enzyme involved in the conversion of capecitabine into 5-fluorouracil and of 5-fluorouracil into its active metabolites; the enzyme is an angiogenic factor 55,56 whose expression is upregulated in atherosclerotic plaques and during myocardial infarction. 21,22 Toxic effects of the drugs could also be caused through endothelial damage, with increased levels of endothelin 1 producing vasospasm and ischemia.…”
Section: Drugs and Mechanismsmentioning
confidence: 99%
“…Thymidine phosphorylase is an enzyme involved in the conversion of capecitabine into 5-fluorouracil and of 5-fluorouracil into its active metabolites; the enzyme is an angiogenic factor 55,56 whose expression is upregulated in atherosclerotic plaques and during myocardial infarction. 21,22 Toxic effects of the drugs could also be caused through endothelial damage, with increased levels of endothelin 1 producing vasospasm and ischemia.…”
Section: Drugs and Mechanismsmentioning
confidence: 99%
“…TP was also found to be an angiogenic factor (known as platelet-derived endothelial cell growth factor) [ 28 , 29 ]. TP expression is up-regulated in atherosclerotic plaques [ 30 ] and during myocardial infarction [ 31 ], potentially contributing to the higher prevalence of cardiotoxicity in patients with previous cardiovascular disease or 5-FU induced damage.…”
Section: Introductionmentioning
confidence: 99%
“…Increased serum levels of CK isoenzymes variously signal heart, brain, or skeletal muscle damage. They may also be markers for advanced tumours with poor prognosis [49]. Which shown that CK-MB level measured by mass assay, is elevated significantly in serum on day I after myocardial infarction in rats, induced by coronary artery ligation.…”
Section: Variablementioning
confidence: 98%